2022
DOI: 10.1007/s00134-022-06881-0
|View full text |Cite
|
Sign up to set email alerts
|

Small wards in the ICU: a favorable measure for controlling the transmission of carbapenem-resistant Klebsiella pneumoniae

Abstract: Purpose: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is one of the leading causes of healthcare-associated infections (HAIs) and is particularly pervasive in intensive care units (ICUs). This study takes ICU layout as the research object, and integrates clinical data and bacterial genome analysis to clarify the role of separate, small wards within the ICU in controlling the transmission of CRKP.Methods: This study prospectively observed the carriage and spread of CRKP from a long-term in-hospital patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…The bla KPC -harboring plasmids in obtaining groups were IncF types and shared the similar gene context of bla KPC with persisting groups. Our work previously confirmed that the pathogenic microorganisms could either being cross-regional transmitted between the environment and humans [ 21 ], or being limited to a specific area [ 22 ]. Above all, we supposed that the bla KPC gene was more likely being transferred from other strains rather than a new clone replacement.…”
Section: Discussionsupporting
confidence: 78%
“…The bla KPC -harboring plasmids in obtaining groups were IncF types and shared the similar gene context of bla KPC with persisting groups. Our work previously confirmed that the pathogenic microorganisms could either being cross-regional transmitted between the environment and humans [ 21 ], or being limited to a specific area [ 22 ]. Above all, we supposed that the bla KPC gene was more likely being transferred from other strains rather than a new clone replacement.…”
Section: Discussionsupporting
confidence: 78%
“…CRKP represents a devastating threat to global public health and clinical settings. [18][19][20] The prevalence of meropenemresistant K. pneumoniae has increased rapidly in China, from 2.9% in 2005 to 24.2% in 2022, according to the China Antimicrobial Surveillance Network (CHINET, http://www.chinets.com/). According to an antimicrobial resistance surveillance study from the Swiss ICU, carbapenem-resistant Enterobacterales (CRE) have been steadily increasing from 1% to 5% between 2008 and 2019.…”
Section: Discussionmentioning
confidence: 99%
“…13 HAI was defined as an infection occurring at least 48 hours after hospitalisation. 14 CAI was defined as an infection that occurred within 48 hours of admission. 15 The clinical outcomes of patients were divided into an improved group (patients, getting better and alive when being discharged) and a poor prognosis group (patients, death or terminal discharge).…”
Section: Antimicrobial Susceptibility Test Clinical Collecting Inform...mentioning
confidence: 99%